The medicinal plant used in the Guangxi Fangcheng Golden Camellias national nature reserve, a coastal region in southern China - Renchuan Hu; Kedao Lai; Binsheng Luo; Renjie Tang; Ruibin Huang; Xiaoxia Ye (Journal of Ethnobiology and Ethnomedicine, 2023)
Abstract Backgrounds Guangxi Fangcheng Golden Camellias national nature reserve, situated in Fangcheng City, Guangxi Province, China, is a coastal region renowned for its exceptional natural environment. Over time, the residents of this area have acquired extensive knowledge regarding medicinal plants, owing to their close association with the abundant flora. Our study aims to document the medicinal plants used by the local community near the Guangxi Fangcheng Golden Camellias national nature reserve. We seek to investigate the unique regional properties, cultural significance, and potential connections between medicinal plants used in surrounding villages and those sold in markets. Methods During 2019–2021, 96 informants, including 36 key informants, were interviewed in the study area. The snowball sampling method was used to select respondents from medicinal markets and villages. Local therapists were defaulted as key informants. A panel discussion was held on the protection and threat of medicinal plants and traditional knowledge. In this study, two quantitative indicators, relative frequency citation (RFC) and informant consensus factor (ICF), were used to analyze the traditional medicinal plants in the study area. Results According to the investigation, a total of 396 species of medicinal plants belonging to 295 genera and 116 families were recorded. From the perspective of Lifeform, herbs accounted for 38.9%, followed by shrubs. Most of the medicinal parts are whole plant (120 species, 25.59%), branches and leaves (116 species, 24.73%), and roots (101 species, 21.54%). Medicinal bath is the most commonly used therapeutic method. Among the 13 therapeutic targets recorded, rheumatic drugs accounted for the highest proportion, followed by muscular system diseases and skin-related diseases, which are closely related to local climate and livelihood. ICF shows that the use of local medicinal plants and related knowledge is very diverse, so local people have more options for treating diseases. Melicope pteleifolia, Clerodendrum cyrtophyllum, Lygodium flexuosum, Elephantopus scaber, Artemisia argyi, Plantago asiatica, Centella asiatica, Grangea maderaspatana, and Liquidambar formosana have high RFC, which are closely connected to local people's daily lives and are potentially vital to them. The wild vegetation, mostly around the nature reserve, is the primary source of medicinal materials sold in the urban medicinal market. Urban areas have fewer varieties of medicinal plants compared to villages near protected areas. However, there is consistency in their usage and application. Conclusion The medicinal plants used in the villages near the Golden Camellia Nature Reserve are diverse, and the relevant traditional knowledge is relatively well preserved. The collection of medicinal materials by local people is sustainable. This study suggests that the local government should also protect relevant traditional knowledge in the decision-making process.